Lymphotoxin-α Plays Only a Minor Role in Host Resistance to Respiratory Infection with Virulent Type A Francisella tularensis in Mice - Deng Zhang; Rhonda KuoLee; Greg Harris; Qinxian Zhang; J. Wayne Conlan; Wangxue Chen (Mediators of Inflammation)
This study examined the role of lymphotoxin (LT)-α in host defense against airborne infection with Francisella tularensis, a gram-negative facultative intracellular bacterium and the causative agent of tularemia. Following a low-dose aerosol infection with the highly virulent type A strain of F. tularensis, mice deficient in LT α (LTα−/−) consistently harbored approximately 10-fold fewer bacteria in their spleens at day 2 and 10-fold more bacteria in their lungs at day 4 than LTα+/+ mice. However, the mortality and median time to death were indistinguishable between the two mouse strains. In addition, the inflammatory responses to the infection, as reflected by the cytokine levels and leukocyte influx in the bronchoalveolar lavage fluid and histopathological analysis, were generally similar between LTα−/− and LTα+/+ mice. These data suggest that although LTα does not contribute significantly to the resistance and host responses of mice to airborne type A F. tularensis infection, it does play a subtle role in the multiplication/dissemination of F. tularensis.